2004
DOI: 10.1242/jcs.01096
|View full text |Cite
|
Sign up to set email alerts
|

PDE4-regulated cAMP degradation controls the assembly of integrin-dependent actin adhesion structures and REF52 cell migration

Abstract: Plating of REF52 cells onto extracellular matrix components leads to the formation of integrin-dependent actin adhesion microspikes. We show that the formation of these structures is sensitive to chemical agents that regulate cAMP levels, such as forskolin and IBMX. In particular, by using the specific inhibitor rolipram, we identify the PDE4 family of cAMP-specific phosphodiesterases as critical regulators of this process. The effect of PDE4 on microspike formation is mediated by actions exerted through the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 61 publications
3
47
0
Order By: Relevance
“…Interestingly, altered motility was paralleled by a reduced capacity for cells to reorganize their actin cytoskeleton, to promote the formation of actin spike, and to change their shape following contact with ECM (46). This result is in line with previous observations showing that hERG expression contributes to morphology, actin cytoskeleton dynamics, and finally cell migration behavior (11).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, altered motility was paralleled by a reduced capacity for cells to reorganize their actin cytoskeleton, to promote the formation of actin spike, and to change their shape following contact with ECM (46). This result is in line with previous observations showing that hERG expression contributes to morphology, actin cytoskeleton dynamics, and finally cell migration behavior (11).…”
Section: Discussionsupporting
confidence: 89%
“…In this context, studies using bovine (bAEC) or human (HUVEC) cells have indicated that increasing VEC cAMP levels may represent a novel therapeutic approach to achieving this goal (Favot et al, 2003;Fleming et al, 2004). Although these earlier studies showed that this approach could work in model systems, they did not assess its potential in microvascular beds, vascular structures that are more likely to be involved in supplying VECs for angiogenesis in vivo in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Most effects of cAMP or cGMP are thought to be related to activation of protein kinase A or protein kinase G, respectively, and phosphorylation of multiple selective cellular substrates (D'Angelo et al, 1997;Fleming et al, 2004). Cellular cAMP and cGMP levels are dynamically regulated by both the rate of their synthesis by cyclases and their hydrolysis by cyclic nucleotide phosphodiesterases (PDEs).…”
mentioning
confidence: 99%
“…Plasmids encoding FLAG-DISC1, mycHIS-fl-DISC1, mycHIS-(⌬1-187)-DISC1, PKA inhibitory peptide PKI, and PDE4 constructs PDE4A5, PDE4B1, PDEB2, PDEB3, PDE4C2, PDE4D3, PDE4D5, PDE4D3S54A, PDE4D3S54E, PDE4D3S13AS54A, and PDE4D-CAT have been described previously (Huston et al, 1996(Huston et al, , 1997Bolger et al, 1997;Owens et al, 1997;Hoffmann et al, 1998;Beard et al, 2000;Brandon et al, 2004;Fleming et al, 2004;Millar et al, 2005). DISC1 regions comprising residues 220 -283 and 359 -854 were subcloned into pEBG-2T vector to generate GST fusion proteins for expression in mammalian cells.…”
Section: Methodsmentioning
confidence: 99%